Developmental persistent falcine sinus with cranium bifidum occultum, craniosynostosis, and associated anomalies: A unique case - Singh, Arvinder; Kaur, Inderpreet (Indian Journal of Case Reports, 2018)
The falcine sinus is an intrauterine anatomic structure located in the falx cerebri that is closed after birth and persistence of thisembryologic falcine sinus is considered as a rare variation of the venous pathway which is associated with defect in the developmentof the straight sinus leading to formation of an alternate venous pathway served by the persistent falcine sinus. Cranium bifidumoccultum is another rare skull ossification disorder referred to as the Catlin mark characterized by ossification defects in theparietal bones. Many other associated anomalies can be seen with persistent falcine sinus apart from cranium bifidum occultumwhich include absent or dysplastic tentorium cerebelli, agenesis of the corpus callosum, apert syndrome, atretic occipital/parietalencephalocele, vein of galen malformation, osteogenesis imperfecta, and chiari malformation Type II. We describe a rare case of a10-year-old girl who presented with short stature, intermittent headache, and abnormal skull shape. On radiological examination,persistent falcine sinus was detected with large midline skull defect at the high parietal area. The straight sinus was absent, and therewas dysplastic tentorium cerebelli. In addition to these, craniosynostosis was also present with many other associated anomalies.Persistent falcine sinus and cranium bifidum occultum are very rare, and when found, they are associated with many anomaliesraising the possibility that they may represent the benign end of the same developmental spectrum. To the best of our knowledge,these constellations of anomalies have been reported in very few children.